2021
DOI: 10.1093/mr/roab027
|View full text |Cite
|
Sign up to set email alerts
|

Structural equation modelling provides insights to understand the construct of chronic pain in women with rheumatoid arthritis

Abstract: Objectives We aimed to adopt a multidimensional approach and investigate the interconnections between biomarkers (cytokines, matrix metalloproteinases, and cortisol) and psychosocial aspects considering pain acceptance, the individual construct of pain perception in terms of blood inflammation biomarkers, anxiety, self-efficacy, and functional performance and to define the quality of life (QoL) in women with rheumatoid arthritis (RA). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“… Mittinty et al (2018) argue that high self-efficacy is one of the most important factors in reducing the severity of chronic pain. Indeed, many researchers note that higher self-efficacy is associated with less intense pain, better adjustment to pain, and improved pain control ( Miles et al, 2011 ; Ruben et al, 2017 ; Vendrusculo-Fangel et al, 2022 ). Sturgeon and Zautra (2010) also observed that high self-efficacy not only reduces the severity of pain in the present moment but also predicts lower pain severity in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Mittinty et al (2018) argue that high self-efficacy is one of the most important factors in reducing the severity of chronic pain. Indeed, many researchers note that higher self-efficacy is associated with less intense pain, better adjustment to pain, and improved pain control ( Miles et al, 2011 ; Ruben et al, 2017 ; Vendrusculo-Fangel et al, 2022 ). Sturgeon and Zautra (2010) also observed that high self-efficacy not only reduces the severity of pain in the present moment but also predicts lower pain severity in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, researchers inquire about the factors contributing to such differences among patients and the phenomena associated with better adjustment and less severe pain. Several studies suggest that various psychosocial factors may influence pain manifestation among patients with RA ( Bergström et al, 2023 ; Bouhouche et al, 2017 ; Rezaei et al, 2014 ; Vendrusculo-Fangel et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of inflammatory diseases, four articles have studied the pathological mechanisms involved in MMP in rheumatoid arthritis (RA) associated with the psychosocial sphere [90,91].…”
Section: Matrix Metalloproteinases: Rheumatoid Arthritis and Psychoso...mentioning
confidence: 99%
“…Vendrusculo et al [91] conducted an observational cross-sectional study to provide a comprehensive description of chronic pain in Brazilian women with rheumatoid arthritis (RA) compared to women without RA or chronic pain, who will serve as the control group.…”
Section: Matrix Metalloproteinases: Rheumatoid Arthritis and Psychoso...mentioning
confidence: 99%
See 1 more Smart Citation